Utilization of Twitter in Customer Relationship Management at PT Bank Syariah Indonesia (BSI) - Setya Indah Isnawati; Jaya Ramadaey Bangsa; Satria Avianda Nurcahyo; Ahmad Ali (AL-ARBAH: Journal of Islamic Finance and Banking, 2022)
The Association of Indonesian Internet Network Operators (APJII) released data, behaviorally, one of the most dominant uses of the internet in Indonesia is to access social media. Twitter is one of the potentials for companies as a means of interacting with consumers, including maintaining good relations and providing education for consumers regarding the products or services owned by the company, including the implementation of Customer Relationship Management. The purpose of this study is to what extent PT Bank Syariah Indonesia (BSI) utilizes Twitter in implementing CRM. The research method uses netnographic studies, where researchers analyze research results based on observations through social media through entree approaches, data collection, data analysis, data interpretation, and member checks. The results of the study show that Twitter plays a very large role in maintaining relationships with customers, especially in the Islamic banking industry. The number of questions, complaints, suggestions and criticisms addressed to BSI as a service industry makes Twitter a forum for filtering customer responses as a CRM implementation.